Characteristics and proposed classification system of posterior pilon fractures. Issue 3 (January 2019) - Zhang, Jianzheng; Wang, Hao; Pen, Cheng; Qu, Wen-chun; Duan, Lida; Ren, Jixin; Li, Lianhua; Liu, Zhi; Sun, Tiansheng
Abstract : Abstract: Posterior pilon fractures involve the medial malleolus (MM). Our purpose was to define the characteristics of posterior pilon fractures, and propose a classification system based on fracture morphology and type of management. The records of patients with posterior pilon fractures treated from 2011 to 2015 were retrospectively reviewed. The injury mechanism, fracture morphology, surgical approach, and follow-up results were reviewed and analyzed. This study was approved by the Institutional Review Board of PLA Army General Hospital. Thirty-six patients, 18 males and 18 females (mean age: 48.9 years) were included in the study. Four characteristics were used to define posterior pilon fractures. A simple posterolateral approach or a combined posterolateral and posteromedial approach was used for reduction and fixation in all patients. The mean follow-up time was 28.2 months, and at the end of follow-up, the mean American Orthopedic Foot and Ankle Society Score (AOFAS) was 82.5 points (range: 35–100 points). Based on injury mechanism and fracture morphology, we classified posterior pilon fractures into 3 types that suggest the optimal surgical approach: type I, a single complete fracture fragment; type II, a posterior malleolus fracture with 2 subtypes; type III, a posterior malleolus fracture associated with complete MM fracture with 2 subtypes. The proposed classification system based on injury mechanism and fracture morphology can guide the surgical approach to maximize outcomes.